PREVALENSI INFEKSI DENGUE BERDASARKAN HASIL PEMERIKSAAN NS1 ANTIGEN PADA PASIEN DI NIKI DIAGNOSTIC CENTER TAHUN 2011-2012 - Maharddhika, D.P.G. Jananuraga; Sutirta Yasa, I Wayan Putu (E-Jurnal Medika Udayana; vol 4 no 12(2015):e-jurnal medika udayana, 2018)
PREVALENCE OF DENGUE INFECTION BASED ON NS1 ANTIGEN EXAMINATION IN PATIENTS AT NIKI DIAGNOSTIC CENTER DURING 2011-2012 Dengue is a disease caused by infection with dengue virus, which is transmitted by mosquitoes and can cause a variety of clinical manifestation, either asymptomatic or mild symptomatic to fatal. To diagnose accurately, early examination is needed. Nonstructural protein 1 (NS1) antigen is one examination that is used as a new biomarker in the early diagnosis of dengue infection. Several studies have been conducted expressing the importance of NS1 antigen as a biomarker because it can be detected before antibodies are formed.The study design was retrospective study by taking the data of patients undergoing examination dengue NS1 antigen in Niki Diagnostic Center in 2011-2012. The sample selection is done by consecutive sampling. The results obtained from the medical records are then presented descriptively with tables and narration.Patients who did a dengue checkup of NS1 antigen in Niki Diagnostic Center in 2011 amounted to 140 people with 63 men (45.0%) and 77 women (55.0%), whereas in 2012 amounted to 285 people with 166 men (58.2%) and 119 women (41.8%). For the age group with the most number of examination of dengue NS1 antigen is infant 0-5 years consists of 74 persons (52.9%) in 2011 and 161 people (58.2%) in 2012.On examination of dengue NS1 antigen in 2011, resulted in positive dengue infection as many as 18 of the 140 people (12.9%) with the largest group of dengue infection consists of 66.7% women and27.8%adulthood18-40 years. In 2012 examination dengue NS1 antigen positive results obtained dengue infection as many as 34 of 285 people (11.9%) with the largest group of dengue infection of 61.8% male and 47.1% adulthood 18-40 years.
Keywords: dengue virus infection, NS1 antigen